Influence of Al2O3 Content on the Melting and Fluidity of Blast Furnace Type Slag with Low TiO2 Content - Hao Liu; Yuelin Qin; Yanhua Yang; Qianying Zhang; Nengyun Deng (Journal of Chemistry)
The increasing usage of iron ores with high Al2O3 content significantly increases the amount of Al2O3 in blast furnace slag and consequently affects its performance. This work uses slag sampled on site to study the effects of changes in Al2O3 content on the fluidity of the CaO–SiO2–Al2O3–MgO–TiO2 slag system that is characterized by high Al2O3 and low TiO2 contents, as well as on the phase transition law during the cooling process. Slag viscosity exhibits a rising trend with an increase in Al2O3 content, and Al2O3 in the tested slag is alkaline. The viscous flow activation energy of molten slag rises from 157 kJ/mol to 172 kJ/mol with an increase in Al2O3 content, and the viscous flow units in the slag become large and complicated. When slag is cooled, the main precipitated phase is melilitite. Spinel, perovskite, and olivine are also observed. The crystallization amount of the melilitite phase decreases constantly with an increase in Al2O3 content.